Pogoji odvzema premoženja nezakonitega izvora - Bošnjak, Marko (Podjetje in delo, 2013)
The author treats conditions of the assets of illicit origin forfeiture, as provided by the act adopted in 2011. In the first step, he strives to identify these conditions, since they are defined neither clearly nor systematically. Equally, they are often presented in a wrong way. Further, the author points out basic human rights affected by the measure, evaluating the intensity and lawfulness of such interference. Several flaws are highlighted, including the fact that the measure is not conditioned by a guilty verdict of a criminal court. Therefore, specific provisions could be found unconstitutional by an eventual constitutional review, while problems in application by the courts are expected.
Keywords: kazniva dejanja; premoženje; zaplemba premoženja